Splicing mutation in Sbf1 causes nonsyndromic male infertility in the rat - Liška, František; Chylíková, Blanka; Janků, Michaela; Šeda, Ondřej; Vernerová, Zdeňka; Pravenec, Michal; Křen, Vladimír (Reproduction (Cambridge, England), 2016)
In the inbred SHR/OlaIpcv rat colony, we identified males with small testicles and inability to reproduce. By selectively breeding their parents, we revealed the infertility to segregate as an autosomal recessive Mendelian character. No other phenotype was observed in males, and females were completely normal. By linkage using a backcross with Brown Norway strain, we mapped the locus to a 1.2Mbp segment on chromosome 7, harboring 35 genes. Sequencing of candidate genes revealed a G to A substitution in a canonical 'AG' splice site of intron 37 in Sbf1 (SET binding factor 1, alias myotubularin-related protein 5). This leads to either skipping exon 38 or shifting splicing one base downstream, invariantly resulting in frameshift, premature stop codon and truncation of the protein. Western blotting using two anti-Sbf1 antibodies revealed absence of the full-length protein in the mutant testis. Testicles of the mutant males were significantly smaller compared with SHR from 4weeks, peaked at 84% wild-type weight at 6weeks and declined afterward to 28%, reflecting massive germ cell loss. Histological examination revealed lower germ cell number; latest observed germ cell stage were round spermatids, resulting in the absence of sperm in the epididymis (azoospermia). SBF1 is a member of a phosphatase family lacking the catalytical activity. It probably modulates the activity of a phosphoinositol phosphatase MTMR2. Human homozygotes or compound heterozygotes for missense SBF1 mutations exhibit Charcot-Marie-Tooth disease (manifested mainly as progressive neuropathy), while a single mouse knockout reported in the literature identified male infertility as the only phenotype manifestation.
Keywords: Gene Expression Regulation; Male; intracelulární signální peptidy a proteiny; mutace; Infertility, Male; potkani inbrední SHR; Intracellular Signaling Peptides and Proteins; mužské pohlaví; krysa rodu Rattus; Animals; alternativní sestřih; ženské pohlaví; zvířata; regulace genové exprese; Rats; Rats, Inbred SHR; Alternative Splicing; Mutation; Female; mužská infertilita